Fernando Osorio do Campo: Report of an Investigation - Biscainho-Fernandes, Carlos-Caetano (Madrygal. Revista de Estudios Gallegos, 2017)
Fernando Osorio do Campo was one of the most outstanding men of the Irmandades da Fala theatrical movement, but this figure remains a mystery for Galician theatrical historiography. The news related to the creation of the Conservatorio Nacional de Arte Galega record his birth in A Coruña as well as the theatrical education he received in Lisbon. However, we know very little about him in the period before 1919 and since 1924 –when he published the play Desourentación–. We know nothing of his passage through life except for Donega’s biographical note published in 1971 “Un home, unha aventura, un tempo”, an article in which future secretary of the Real Academia Galega (Galician Academy) collects surprising moments of an intense life across three continents and informs of plays by Osorio still unpublished. In this paper, we report the research process carried out since 2008 through half a dozen countries on life and plays of Fernando Osorio, on the meaning of making a biography, on the investigative techniques used to achieve the goal of constructing a documented Osorio’s story, as well as of publishing and disseminating the fortunately found plays.
Keywords: Fernando Osorio; National Galician Art Conservatory; Biographical Research; Biographeme; Life Story; Narrative Identify.